Relationship Of Oncology Nurses’ Knowledge And Self-Efficacy With The Quality Of Life (Qol) Of Cancer Patients In Punjab, Pakistan: An Empirical Investigation - Tahira Aslam , Samina Kausar , Zunaira Aziz , Shazia Taj , Fouzia Sattar , Rifat Yasmeen (Migration Letters, 2024)
It is hypothesized that oncology nurses’ knowledge and self-efficacy play an instrumental role in improving the Quality of Life (QoL) of cancer patients. Thus, this study was conducted to investigate the strength of the relationship of oncology nurses’ knowledge and self-efficacy with the quality of life of cancer patients. The cross-sectional analytical research design was used. The nurses working in oncology centers & cancer patients of stage III and stage IV were considered as the study population. The non-probability purposive sampling was used. The sample of 150 oncology nurses and 150 cancer patients was selected from the five hospitals in Punjab, Pakistan. The analysis yi[1]elded that the mean knowledge score among oncology nurses regarding palliative care was 8.78 ± 2.31. The nurses also had a mean self-efficacy score of 33.6 ± 7.85. Notably, 72.0% of cancer patients (n=108) experienced poor quality of life, while 28.0% (n=42) reported an average quality of life. Statistical analysis revealed significant relationships between nurses’ knowledge and self-efficacy in palliative care (p=0.044) and between nurses’ knowledge and the quality of life of cancer patients (p=0.013) Conclusion: Palliative care-experienced nurses with adequate knowledge and high self-efficacy yields improved outcomes and enhance the quality of life for advanced cancer patients, emphasizing the value of healthcare organizations prioritizing nurse expertise.